2015
DOI: 10.1590/2359-3997000000008
|View full text |Cite
|
Sign up to set email alerts
|

The association of autoimmune thyroiditis and non-functional adrenal incidentalomas with insulin resistance

Abstract: Objective: Patients with incidental nonfunctioning adrenal adenoma are associated with increased risk of obesity, impaired glucose tolerance and dyslipidemia. We aimed to investigate the relationship between thyroid function, serum lipids and insulin resistance in patients with nonfunctioning adrenal incidentaloma. Subjects and methods: Forty patients who had diagnosed as adrenal incidentaloma (AI) in our department were included in the study. Serum free triiodothyronine (fT3), free thyroxine (fT4), thyroid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
2
1
1
Order By: Relevance
“…In a study by Karaköse et al with NFAI patients, they reported that fT4, antithyroglobulin, and anti-TPO levels were significantly higher in the NFAI group compared to the control group, whereas, thyroid volumes, TSH, and fT3 levels were comparable in both the groups. Moreover, they determined a significant relationship between HOMA-IR levels and thyroid volume and fT4 levels (24). The present study failed to obtain any difference between NFAI and control groups in terms of TSH, fT4, and anti-TPO levels.…”
Section: Nfai (N=54)contrasting
confidence: 73%
“…In a study by Karaköse et al with NFAI patients, they reported that fT4, antithyroglobulin, and anti-TPO levels were significantly higher in the NFAI group compared to the control group, whereas, thyroid volumes, TSH, and fT3 levels were comparable in both the groups. Moreover, they determined a significant relationship between HOMA-IR levels and thyroid volume and fT4 levels (24). The present study failed to obtain any difference between NFAI and control groups in terms of TSH, fT4, and anti-TPO levels.…”
Section: Nfai (N=54)contrasting
confidence: 73%
“…The association between adrenal mass and thyroid has been evaluated in several studies. It has been found that the frequency of autoimmune thyroid disease increases (6,23), and thyroid nodules are more common (6) in AI patients, and this situation is frequently related to the underlying IR. The co-existence of adrenal and thyroid incidentaloma may be due to increased and widespread use of advanced radiologic imaging devices (24).…”
Section: Discussionmentioning
confidence: 99%
“…In light of the presented literature data, is it possible that insulin resistance and hyperinsulinemia may be among the factors contributing to the coexistence of HD and AIs? In a study by Karakose et al, patients with AIs had higher HOMA-IR, hs-CRP and ft4 levels and anti-TPO and anti-TG titers than the control group [ 57 ]. Moreover, in the group of AI patients, a positive correlation was observed between HOMA-IR, hs-CR and ft4 and the volume of the thyroid.…”
Section: Insulin Resistancementioning
confidence: 99%